Appaloosas - Stone, Lynn M. (Vero Beach, Fla. : Rourke Corp., 1998)
Describes the history and physical appearance of the spotted horses that were prized by the Nez Perce and have become a very popular breed in the United States today.
Includes index.
900L
Keywords: Appaloosa horse; Horses